More Hype Than Substance? A Meta-Analysis on Job and Task Rotation - Mlekus, Lisa; Maier, Günter W. (Frontiers in Psychology, 2021)
Although there exist numerous publications on job and task rotation from various disciplines, there is no consistent evidence of their effectiveness. Drawing on theories from industrial and organizational psychology, knowledge management, ergonomics, and management science, we meta-analytically investigated relationships between job/task rotation and employee attitudes, learning and development, psychological and physical health, and organizational performance. Due to a conceptual overlap and frequent confusion of terminology, we analyzed the design of the rotation (job rotation vs. task rotation) as a possible moderator. The meta-analysis on 56 studies (N = 284,086) showed that rotation was significantly associated with job satisfaction (r = .27), organizational commitment (r = .16), career success (r = .31), labor flexibility (r = .32), general psychological health (r = .20), stress/burnout (r = −.13), individual performance (r = .13), and productivity (r = .13). Positive relationships between rotation and physical health could only be found when rotation was compared to high-intensity work. Task rotation yielded stronger relationships with attitudinal outcomes, job rotation with learning and development, psychological health, and organizational performance outcomes. Further moderator analyses showed that individualism decreased relationships between task rotation and attitudes, and correlations with organizational performance and physical health were stronger for subjective measures. The findings indicate that many expectations towards job and task rotation are not fully supported.